Biomedical applications of iron sulfide-based nanozymes - Shan, Yunyi; Lu, Wenjie; Xi, Juqun; Qian, Yayun (Frontiers in Chemistry, 2022)
Nanozymes have attracted great interest owing to their marvelous advantages, such as high stability, facile preparation, and high tunability. In particular, iron sulfide-based nanozymes (termed as ISNs), as one of the most researched nanomaterials with versatile enzyme-mimicking properties, have proved their potential in biomedical applications. In this mini-review, we briefly summarize the classification, catalytic mechanisms of ISNs and then principally introduce ISNs’ biomedical applications in biosensors, tumor therapy, antibacterial therapy, and others, demonstrating that ISNs have promising potential for alleviating human health.